1980
DOI: 10.1038/288363a0
|View full text |Cite
|
Sign up to set email alerts
|

Cortical binocularity in infants

Abstract: The primate visual cortex, including that of man, receives separate input from each eye and these interact in binocular cortical neurones. This organization is known to be vulnerable to disruption in early life. To understand the development of human visual cortex, and to detect and assess disorders of binocular function at the earliest possible age, a robust method is needed for detecting binocular interactions in the infant's visual system. We have done this by recording cortical visual evoked responses (VER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
38
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(43 citation statements)
references
References 8 publications
1
38
0
2
Order By: Relevance
“…Studies in nonhuman primates suggest that the sensitive period for binocular vision may be substantially longer than for other aspects of vision such as spectral sensitivity. 62 In healthy controls, although cyclopean stereo vision can be demonstrated in infants at B3 months, 63,64 stereoacuity continues to improve up to the age of B10 years. [65][66][67][68][69][70] This long period of plasticity implies that binocular vision remains vulnerable to disruption until later in development, for example, by the onset of accommodative esotropia in toddlerhood.…”
Section: The Clinical Importance Of Stereoacuity Measurementsmentioning
confidence: 99%
“…Studies in nonhuman primates suggest that the sensitive period for binocular vision may be substantially longer than for other aspects of vision such as spectral sensitivity. 62 In healthy controls, although cyclopean stereo vision can be demonstrated in infants at B3 months, 63,64 stereoacuity continues to improve up to the age of B10 years. [65][66][67][68][69][70] This long period of plasticity implies that binocular vision remains vulnerable to disruption until later in development, for example, by the onset of accommodative esotropia in toddlerhood.…”
Section: The Clinical Importance Of Stereoacuity Measurementsmentioning
confidence: 99%
“…The VEP protocol is useful to avoid difficulties and artifacts arising from behavioral estimation of onset times in a preverbal population, such as infants. DRDC stimuli are faultless probes of binocular function because the alternation of the stimulus can only be detected by subjects with intact cortical binocular function (8,9). DRDCs alternated at 1.875 Hz between binocularly correlated and anticorrelated phases, resulting in a pulsating percept.…”
mentioning
confidence: 99%
“…The recorded VEPs were analyzed in the time and frequency domain, as we have described it previously (11). Although it has been debated whether VEP responses to the alternation of correlated/anticorrelated dynamic random dots are a sign of stereopsis in monkeys (13), recordings in adult human subjects and older children indicated that this response only occurs in subjects with intact binocular function (8,9,11). Previous studies have shown that DRDC-VEP response has an abrupt onset between 3 and 6 mo of age (8-10), and it is followed by the rapid development of stereopsis to "near-adult" level by 6-7 mo in humans (10).…”
mentioning
confidence: 99%
See 2 more Smart Citations